(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
All patients were divided into 3 groups: Group 1: Allergic rhinitis, persistent form. Adenoiditis. Hypertrophy of the pharyngeal tonsil of the II — III degree; group 2: Allergic rhinitis, persistent form. Adenoiditis. Hypertrophy of the pharyngeal tonsil of the II - III degree. The comparison group included patients diagnosed with adenoiditis. Pharyngeal tonsil hypertrophy of II - III degree without signs of atopy. Microbiological examination of the nasal cavity was performed in patients with adenoiditis with AR and patients with adenoiditis without atopy. Bacteriological examination of nasal secretions revealed in patients with allergic rhinitis complicated by adenoiditis, a wide species diversity of microflora with a high degree of colonization.